Anne Rogerson, Virgil’s Ascanius. Imagining the Future in the Aeneid, Cambridge, Cambridge University Press, 2017, 237 + viii pp. ISBN: 978-1-107-11539-2. - Cairo, María Emilia (Revista de Estudios Latinos, 2018)